Comparative Analysis and Optimization of GIS-Based Rooftop Solar Power Plants - Ikhsan Hidayat; Sardi Salim; Ade Irawaty Tolago; Yasin Mohamad; Zainudin Bonok (Jambura Journal of Electrical and Electronics Engineering, 2026)
The increasing demand for electricity and the global commitment to carbon reduction have encouraged higher education institutions to integrate renewable energy into campus infrastructures. However, most previous rooftop PV studies at Universitas Negeri Gorontalo (UNG) have been limited to single-building assessments or have not fully integrated spatial analysis with technical simulation. This study addresses this research gap by conducting a comparative analysis and system optimization of a rooftop photovoltaic (PV) installation at the Faculty of Engineering building using a combined Geographic Information System (GIS) approach and detailed technical simulation through HelioScope. The optimized design yields a total capacity of 368.79 kWp comprising 647 Canadian Solar 570W modules. Simulation results indicate an annual energy output of 486.5 MWh with a Performance Ratio (PR) of 95.8%, where PR represents the ratio of actual system performance to ideal irradiance conditions, and a solar access value of 99.2%. The economic assessment shows a payback period of 11.04 years under an export tariff of IDR 1,440/kWh. Furthermore, a comparative evaluation with two previous studies demonstrates significant improvements in both technical and economic aspects due to the integrated GIS and high-resolution simulation approach. The findings provide a valuable reference for advancing renewable energy implementation in educational institutions, particularly in designing efficient and sustainable rooftop PV systems.